2013
DOI: 10.1371/journal.pone.0078336
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Identifying Neisseria meningitidis Carriers: A Multi-Center Study in the African Meningitis Belt

Abstract: ObjectiveDetection of meningococcal carriers is key to understanding the epidemiology of Neisseria meningitidis, yet no gold standard has been established. Here, we directly compare two methods for collecting pharyngeal swabs to identify meningococcal carriers.MethodsWe conducted cross-sectional surveys of schoolchildren at multiple sites in Africa to compare swabbing the posterior pharynx behind the uvula (U) to swabbing the posterior pharynx behind the uvula plus one tonsil (T). Swabs were cultured immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
2
21
1
Order By: Relevance
“…The prevalence of N. meningitidis in our study had a high carriage rate than three studies conducted in Mali, with oropharyngeal carriage of 5%, 7.7%, and 6.9% [11,26,27] respectively. The predominant serogroup was none-serogroupabable and serogroup A was not identified.…”
Section: Discussioncontrasting
confidence: 53%
“…The prevalence of N. meningitidis in our study had a high carriage rate than three studies conducted in Mali, with oropharyngeal carriage of 5%, 7.7%, and 6.9% [11,26,27] respectively. The predominant serogroup was none-serogroupabable and serogroup A was not identified.…”
Section: Discussioncontrasting
confidence: 53%
“…Regarding the sampling methods throat sampling is clearly the sampling method of choice, which is consistent with previous studies . In addition, sensitivity can be improved by using PCR, which is more sensitive than culture for identification of asymptomatic carriers .…”
Section: Discussionsupporting
confidence: 84%
“…Among studies that used the oropharyngeal approach, swabbing of solely the posterior pharyngeal wall was used in two studies whilst in the remainder both the posterior pharynx and the tonsils were swabbed. A comparative study conducted in Mali showed no significant difference in the prevalence of pharyngeal carriage of N. meningitidis using either of these two methods .…”
Section: Resultsmentioning
confidence: 96%